Polyhydroxybutyrate-co-hydroxyvalerate structures loaded with adipose stem cells promote skin healing with reduced scarring. (15th April 2015) - Zonari, Alessandra; Martins, Thaís M.M.; Paula, Ana Cláudia C.; Boeloni, Jankerle N.; Novikoff, Silviene; Marques, Alexandra P.; Correlo, Vitor M.; Reis, Rui L.; Goes, Alfredo M.
Graphical abstract: Abstract: Currently available skin substitutes are still associated with a range of problems including poor engraftment resulting from deficient vascularization, and excessive scar formation, among others. Trying to overcome these issues, this work proposes the combination of poly(3-hydroxybutyrate-co-hydroxyvalerate) (PHBV) structures with adipose-derived stem cells (ASCs) to offer biomechanical and biochemical signaling cues necessary to improve wound healing in a full-thickness model. PHBV scaffold maintained the wound moisture and demonstrated enough mechanical properties to withstand wound contraction. Also, exudate and inflammatory cell infiltration enhanced the degradation of the structure, and thus healing progression. After 28 days all the wounds were closed and the PHBV scaffold was completely degraded. The transplanted ASCs were detected in the wound area only at day 7, correlating with an up-regulation of VEGF and bFGF at this time point that consequently led to a significant higher vessel density in the group that received the PHBV loaded with ASCs. Subsequently, the dermis formed in the presence of the PHBV loaded with ASCs possesses a more complex collagen structure. Additionally, an anti-scarring effect was observed in the presence of the PHBV scaffold indicated by a down-regulation of TGF-β1 and α-SMA together with an increase of TGF-β3, when associated with ASCs. These results indicate that although PHBV scaffold was able to guide the wound healing process with reduced scarring, the presence of ASCs was crucial to enhance vascularization and provide a better quality neo-skin. Therefore, we can conclude that PHBV loaded with ASCs possesses the necessary bioactive cues to improve wound healing with reduced scarring.